Mapping Of Tsunami Risk Zones On Lombok Island To Support Military Operations Other Than War (OMSP) - Riyan Eko Prasetiyo; Gita Amperiawan; Ansori, Ansori (CV. AFDIFAL MAJU BERKAH, 2024)
Indonesia's existence at the meeting point of three major plates has resulted in the creation of tectonic complexes, especially at plate boundaries located in eastern Indonesia. Lombok Island and its surroundings have an active seismicity zone, namely the Flores back arc and the subduction between the Indo-Australian and Eurasian plates. The existence of active seismicity zones can produce earthquake events. If an earthquake occurs in a marine area, there will be high, destructive sea waves called a tsunami and can endanger safety, for this reason it is necessary to carry out tsunami simulations to map vulnerable areas around the coast. This information can then be used to increase community preparedness so that it can support the government in carrying out Military Operations Other Than War (OMSP). The simulation was carried out by integrating modeling software, namely WinITB v.6.52 and ArcGIS mapping software. The simulation results show that the tsunami in the north of Lombok Island and its surroundings spread towards an azimuth angle of 61° and the tsunami in the south of Lombok Island and its surroundings spread towards an azimuth angle of 80°. The estimated height resulting from the tsunami in the north of Lombok Island and its surroundings is as high as 1.9 m with a dangerous classification, while the height resulting from the tsunami in the south of Lombok Island and its surroundings is as high as 4.7 m with a very dangerous classification. Tsunamis can be generated from active seismic sources, with earthquakes with depths of less than 60 km, dip-slip plate faults and earthquake magnitudes greater than M6.5